Exploring Green Entrepreneurship Research Among University Students: A Bibliometric Perspective on Trends and Future Directions - Prasetio, Bayu; Supardi, Endang; Waspada, Ikaputera; Istikomah, Navik (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: Awareness of sustainability and environmentally friendly practices was increasing in various sectors, including the business world, which had led to the development of green entrepreneurship as a sustainable economic strategy. Despite the growing interest of students in green entrepreneurship, there was still a gap in the literature regarding research trends in this area, which called for a systematic approach to understanding the pattern and direction of its development.Purpose: This study aims to analyze and map the development of green entrepreneurship research among university students through a bibliometric approach. It highlights publication trends, patterns of academic collaboration, and the main topics that dominate the scientific literature.Design/methodology/approach: This study employs a bibliometric analysis of 30 selected publications from the Scopus database to examine the development of green entrepreneurship research among university students. Using VOSviewer and R Studio (Bibliometrix) to map citation networks, research trends, and thematic clusters, the study adopts the theoretical framework of entrepreneurial intention and sustainability to provide a structured understanding of this emerging field. Findings/Result: This study confirms that university students are pivotal in shaping green entrepreneurship through sustainability-oriented education, psychological readiness, and institutional support. These findings highlight the need for universities and policymakers to integrate sustainability values into curricula and provide targeted programs that accelerate students’ transition into green entrepreneurial practices.Conclusion: This study concludes that green entrepreneurship among university students is increasingly shaped by sustainability awareness, psychological drivers, and the integration of entrepreneurship education with environmental values. Universities function as central incubators by embedding sustainability into curricula, fostering experiential learning, and facilitating collaborations with industry to enhance students’ readiness for green ventures. For policymakers, these findings emphasize the urgency of providing supportive regulations, accessible green technologies, and cross-sectoral partnerships to accelerate sustainable entrepreneurship as a pathway to inclusive and environmentally responsible economic growth.Originality/value (State of the art): This study highlights the novelty of applying these principles to entrepreneurship education, expanding the traditional intensity model by integrating environmental awareness and moral responsibility as reinforcing mechanisms. By positioning universities as central incubators connecting education, policy, and industry, this study advances understanding of how academic ecosystems can foster green student entrepreneurial orientation more effectively than previous approaches focused solely on economic concepts. Keyword: green entrepreneurship, university students, bibliometric, academic collaboration, sustainability